Quantitative Study of Potential Induced Degradation of a Roof-Top PV-Installation with IR-Imaging - Buerhop-Lutz, Claudia; Pickel, Tobias; Fecher, Frank W.; Zetzmann, Cornelia; Hauch, Jens; Camus, Christian; Brabec, Christoph (33rd European Photovoltaic Solar Energy Conference and Exhibition, 2017)
Potential induced degradation (PID) causes severe damage and financial losses even in modern PVinstallations. In Germany, approximately 19% of PV-installations suffer from PID and resulting power loss. This paper focuses on the impact of PID in real installations. The analysis focuses exemplarily on a 314 kWp PV-system in the Atlantic coastal climate. Infrared (IR)-imaging is used for identifying PID without operation interruption. Historic electric performance monitoring data for several years are analyzed on system and string level. Additionally, punctually measured module string current-voltage (I-V)-curves are considered. The data sets are combined for understanding the PID behavior of this PV plant. The number of PID affected cells within a string varies strongly between 1 to 22% with the string position on the building complex. A PID-resistance which correlates to the defined PID-defect-ration is presented. Finally, indicators for the reliable determination of PID is given.
Keywords: potential induced degradation (PID); IR-imaging; PID criteria; power loss; PID-resistance